2016
DOI: 10.1111/are.13192
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary supplementation of palm fruit extracts on the transcriptomes of growth, antioxidant enzyme and immune-related genes in common carp (Cyprinus carpio ) fingerlings

Abstract: This study investigates the effects of date palm extracts [DPE] (Phoenix dactylifera L. Arecaceae) on growth, immune function and antioxidant system in common carp fingerlings (Cyprinus carpio). One hundred and twenty fish (4.06 ± 0.13 g) were divided into six groups fed on control diet or diets containing 200 mL kg−1 DPE for 8 weeks. At the end of feeding trial, the expression of different genes was measured. Selected genes were grouped into three categories: growth factor genes in brain and liver [growth hor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(31 citation statements)
references
References 48 publications
6
25
0
Order By: Relevance
“…In our study, the amount of GPx did not change. Similar to our study, the In other studies, the effect of natural feed additives increased GPx levels in the liver (Elabd, Wang, Shaheen, Yao, & Abbass, 2016;Hoseinifar et al, 2017a), spleen (E. Yilmaz, 2019) and skin of fish (Hoseinifar et al, 2017b). In our study, SOD and CAT quantities increased significantly in the experimental groups compared with the control group.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In our study, the amount of GPx did not change. Similar to our study, the In other studies, the effect of natural feed additives increased GPx levels in the liver (Elabd, Wang, Shaheen, Yao, & Abbass, 2016;Hoseinifar et al, 2017a), spleen (E. Yilmaz, 2019) and skin of fish (Hoseinifar et al, 2017b). In our study, SOD and CAT quantities increased significantly in the experimental groups compared with the control group.…”
Section: Discussionsupporting
confidence: 91%
“…Similar to our study, the GPx activity of shrimp fed a diet enriched with 0.01% herbal extract did not show a significant change in the 2nd and 4th weeks of the trial (Harikrishnan et al, ; Harikrishnan, Balasundaram, & Heo, ; Harikrishnan, Balasundaram, Jawahar, & Heo, ). In other studies, the effect of natural feed additives increased GPx levels in the liver (Elabd, Wang, Shaheen, Yao, & Abbass, ; Hoseinifar et al, ), spleen (E. Yilmaz, ) and skin of fish (Hoseinifar et al, ). In our study, SOD and CAT quantities increased significantly in the experimental groups compared with the control group.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…In the present study, 0.4% Indian lotus induced significant up‐regulation to IL‐1β and TNF‐α expression levels in tilapia ( p < 0.05). Similar up‐regulation of cytokine genes have been previously reported in Nile tilapia fed on holy basil, Ocimum sanctum, extract (Panprommin, Kaewpunnin, & Insee, ), common carp fed on date palm extracts, Phoenix dactylifera L. Arecaceae and loquat leaf extract, Eriobotrya japonica (Hoseinifar, Dadar, Khalili, Cerezuela, & Esteban, ; Hoseinifar, Zou, Doan, Miandare, & Hoseini, ). However, down‐regulation of the expression levels of these genes was observed in 0.1% and 0.2% Indian lotus‐supplemented groups.…”
Section: Discussionsupporting
confidence: 79%
“…In prebiotics research in fish, not much has been carried out on the effects of these dietary supplements in the antioxidant status in fish. However, in a recent study involving probiotics and palm fruit extracts showed that these dietary supplements altered the expression of selected antioxidant genes: superoxide dismutase (SOD), catalase (CAT) and GR particularly in the gills and skin of gilthead seabream, Sparus aurata (Esteban et al., ) and common carp (Hoseinifar, Dadar, Khalili, Cerezuela & Esteban, ). These preliminary findings seem to indicate that prebiotics have important roles in the antioxidant capacity in various organisms when incorporated in the feed.…”
Section: Discussionmentioning
confidence: 99%